Shaka : King of the Zulus - Stanley, Diane; Vennema, Peter (New York : Morrow Junior Books, 1988)
A biography of the nineteenth-century military genius and Zulu chief.
Bibliography: p. [40].
Keywords: Chaka, -- Zulu Chief, -- 1787?-1828 -- Juvenile literature; Chaka, -- Zulu Chief, -- 1787?-1828; Zulu (African people) -- Kings and rulers; Zulu (African people) -- History; Zulus -- Biography; Zulus -- Kings and rulers; Zulus -- History; Zulus -- Kings, queens, rulers, etc; Zulus -- History; Zulus -- History; Chaka, Zulu Chief, 1787?-1828; South Africa -- Kings, queens, rulers, etc